An appraisal of political beliefs and trust-in-government among market women in marginalised communities in Ondo city (2025)
Women’s participation in Nigerian politics remains depressingly low, yet Nigeria’s political history shows that market women have not always been silent political actors. The study, therefore, investigated an appraisal of political beliefs and trust in government among market women in marginalised communities in Ondo city. Previous studies have largely concentrated on women’s empowerment and political interest, with little attention paid to the political beliefs and trust orientations of market women. The study adopted a descriptive research design, with 210 market women randomly selected as participants. Data were collected using the Political Belief Scale (PB, r = 0.94) and Trust-in-Government Scale (T-I-G, r = 0.81). Quantitative data were analysed using descriptive statistics. Participants’ mean age was 52±1.05 years, and 21.1% were between 50–54 years of age. Results revealed a paradox: while political beliefs were high (x̄ = 2.95), trust in government was low (x̄ = 2.47), against the threshold of 2.5. These findings imply that although market women demonstrate strong political beliefs, their limited trust in government could hinder sustained participation in democratic governance. It is concluded that bridging this gap requires deliberate trust-building mechanisms. The study recommends the establishment of permanent liaison committees between local government councils and market associations (Iyalojas, cooperative leaders) to enable two-way communication on policy priorities, infrastructure needs, and market regulations.